Aquaculture Database System for Culture Practices - Mahalakshmi, P.; Panigrahi, A.; Ghoshal, T. K.; Biswas, G.; Ananda Raja, R.; Kumar, Sujeet (Fishery Technology, 2018)
Aquaculture Database System was developed forthe management of information on aquaculturepractices collected by the research institutes andother organizations using Integrated DevelopmentEnvironment of software. In this system, 29 tablesand their corresponding relationships were designedby one-to-one mapping cardinality. The mainscreen was designed into four modules namely,Entry, Search, User Manual and Exit. The entrymodule allows the user to add culture practicesinformation into their corresponding table forstoring. The search module allows the user toretrieve the required information from their correspondingtables. The results can be displayed in thereport format and also it can be exported toMSWord or MSExcel. In addition, the basic statisticalanalyses like frequency, percentage, mean andstandard deviation was designed in the outputscreen based on their requirements. The system hasbeen tested using the farm data collected from thebrackishwater aquaculture area in West Bengal.Although illustrations are based on the brackishwater,ADS is general and can act as a model to captureand analyze the data for all other aquaculturepractices.